2014
DOI: 10.1128/jvi.01596-14
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Retroviral Envelope Spikes in Complex with the V3 Loop Antibody 447-52D on Intact Viruses by Cryo-Electron Tomography

Abstract: The gp120 portion of the envelope spike on human immunodeficiency virus type 1 (HIV-1) plays a critical role in viral entry into host cells and is a key target for the humoral immune response, and yet many structural details remain elusive. We have used cryoelectron tomography to visualize the binding of the broadly neutralizing monoclonal antibody (MAb) 447-52D to intact envelope spikes on virions of HIV-1 MN strain. Antibody 447-52D has previously been shown to bind to the tip of the V3 loop. Our results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 91 publications
(126 reference statements)
2
4
0
Order By: Relevance
“…We found that V3 peptide binding was again associated with tier 1A NAb titers ( P = .0035 and R = 0.72, Spearman rank correlation test) (Figure 5 C), whereas binding to CC loop and cytoplasmic tail peptides were not. These data are consistent with the reported exquisite sensitivity of SF162.LS and MW965.26 to the monoclonal antibody 447-52D (<0.02 ID 50 titer [µg/L]) [ 8 ], a well described V3-loop antibody [ 12 , 13 ], as well as the sensitivity of TH023.6 to V3-specific neutralizing antibodies isolated from subjects in the RV144 vaccine trial [ 14 ].…”
Section: Resultssupporting
confidence: 87%
“…We found that V3 peptide binding was again associated with tier 1A NAb titers ( P = .0035 and R = 0.72, Spearman rank correlation test) (Figure 5 C), whereas binding to CC loop and cytoplasmic tail peptides were not. These data are consistent with the reported exquisite sensitivity of SF162.LS and MW965.26 to the monoclonal antibody 447-52D (<0.02 ID 50 titer [µg/L]) [ 8 ], a well described V3-loop antibody [ 12 , 13 ], as well as the sensitivity of TH023.6 to V3-specific neutralizing antibodies isolated from subjects in the RV144 vaccine trial [ 14 ].…”
Section: Resultssupporting
confidence: 87%
“…In the present case and one described previously (66), spike analysis by more conventional methods produced what can be described as "watered-down" versions of the class averages reported here, which indicated that incomplete ligand binding and/or conformational mobility was operating. Just how incomplete the ligand binding was can be seen in Fig.…”
supporting
confidence: 74%
“…An important mechanism for neutralization resistance derives from the strain-specific shielding of V3 by the V1/V2 loop (55)(56)(57)(58)(59)(60)(61)(62)(63)(64). The interactions of several antibodies with the HIV-1 V3 loop have been studied at the structural level (7,13,17,20,40,65,66), but there are currently no structural studies of antibody interactions with the V3 loop of SIV gp120.…”
mentioning
confidence: 99%
“…Already, the feasibility of antibody labeling for purified macromolecules, viruses, and isolated organelles has been demonstrated (Beck et al 2007;Roos et al 1996). These studies have enabled investigators to determine the 3D structures of low molecular weight proteins by single particle cryo-EM (Wu et al 2012), where proteins localize on specific regions of a virus (Roos et al 1996), and the structural rearrangements that occur when a neutralizing antibody binds with the target antigen Dutta et al 2014;Harris et al 2013;Lin et al 2013;Tran et al 2012). However, similar procedures have not been widely applied to studies of whole, intact mammalian cells because of the concerns associated with retaining cell viability during immunolabeling; the thicknesses of cells and the impact this has on cryo-preservation and cryo-EM imaging; and early reports of antibodyinduced membrane protein 'capping' on live cells (Ash et al 1977;Ferrante and Thong 1979).…”
Section: Introductionmentioning
confidence: 99%